Optimizing the Cost of Process as a Decision-Making Tool to Determine the Selling Price: Case Study on Tenun Ikat Medali Mas Company - Prasaja, Mukti; Lestari, Rufaidho Dwi; Nurrohman, Aan (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
This study aims to find out the cost of production completely and using the process costing method, then determine the selling price of the product using the cost plus pricing approach. The data sources used are primary and secondary data. The data used is descriptive quantitative research. The analysis technique used in this study is descriptive with a quantitative approach, with stages namely grouping data based on cost classification, calculating the cost of production with the process costing method, calculating the selling price with the cost-plus pricing approach, and comparing the calculation of MSMEs Tenun Ikat Medali Mas with the researcher's calculation. This study's results show that the production cost is lower than that of average MSMEs. This indicates the company's ability to accurately calculate the production cost to enhance the company's efficiency. Keywords: Cost of Production; Selling Price; Process costing; Cost-plus Pricing; MSMEs